2012
DOI: 10.1016/j.breast.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Survival and clinicopathological characteristics of breast cancer patient according to different tumour subtypes as determined by hormone receptor and Her2 immunohistochemistry. A single institution survey spanning 1998 to 2010

Abstract: As far as recent breast cancer molecular subtype classification is concerned, much work has dealt with clinical outcomes for triple negative and Her2 patients. Less is known about the course of patients in the remaining subtypes. Molecular classification based on immunohistochemistry is widely available and correlates well with genetic microarray assessment, but at a lower cost. The aim of our investigation was to correlate immunohistochemical subtypes of breast cancer with clinical characteristics and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 41 publications
4
23
1
Order By: Relevance
“…In the present study, the non-luminal HER2-positive group did not tend to show a marker for contralateral breast cancer, in contrast to the aforementioned study. In terms of distant metastasis, the results of the present study were not in agreement with those of the earlier study, which reported that the non-luminal HER2-positive and triple negative subtypes were associated with a high risk of recurrence, rather than the luminal subtypes (García Fernández et al, 2012). There were no statically significant differences between the non-luminal HER2-positive subtype and the other subtypes, except for the luminal A subtype, despite our having observed that the non-luminal HER2-positive subtype was associated with a higher rate of distant metastasis than the other subtypes.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In the present study, the non-luminal HER2-positive group did not tend to show a marker for contralateral breast cancer, in contrast to the aforementioned study. In terms of distant metastasis, the results of the present study were not in agreement with those of the earlier study, which reported that the non-luminal HER2-positive and triple negative subtypes were associated with a high risk of recurrence, rather than the luminal subtypes (García Fernández et al, 2012). There were no statically significant differences between the non-luminal HER2-positive subtype and the other subtypes, except for the luminal A subtype, despite our having observed that the non-luminal HER2-positive subtype was associated with a higher rate of distant metastasis than the other subtypes.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to the results of the present study, the study found that the triple negative subtype was an independent predictor of distant metastasis with statistical significance. García Fernández et al (2012) observed in a large cohort study that luminal tumors had a significantly smaller chance of distant metastasis than nonluminal HER2-positive and triple negative tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there has been increasing attention to new molecular classifications of BC, based on the genetic map (3,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), which can improve the prognostic power with low cost and high accessibility. In fact, IHC classification can improve the prognostic and therapeutic approaches (3,44).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is one of the most commonly diagnosed cancers among women worldwide (1)(2)(3). The prevalence of BC is increasing in both developed and developing countries (4), accounting for 19% -34% of all cancer cases among women around the world (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation